Changes in toxicity and dioxin-like activity of sediments from the Tietê River (São Paulo, Brazil) - Rocha, Paula Suares; Storch, Volker; Braunbeck, Thomas (Ecotoxicology and environmental safety, 2010)
Acute cytotoxicity (neutral red assay), AhR-mediated toxicity (CYP P450 1A induction potential—EROD assay) and concentrations of PAHs were recorded in RTL-W1 cells to assess the ecotoxicological potential of sediments from reservoirs along the Tietê River and the Pinheiros River (Brazil). Almost all sediments tested induced cytotoxicity and stimulated cytochrome P450-associated EROD activity. Toxicity increases from Tietê River spring to São Paulo city region and decreases towards downstream. A closer analysis of chemical measurements of PAHs and results from bioassay revealed that the PAHs analyzed could not explain more than 7% of the EROD-inducing potencies. Results confirm that most of the toxicity is due to the discharges of the metropolitan area of São Paulo. Moreover, they indicate additional sources of pollutants along the river course, which contribute to the degradation of each reservoir.